The Effect of Surface Friction on the Seismic Response of Isolated Structures With Triple Friction Pendulum Bearings - ALJALAB, RAWAN (İstanbul Kültür Üniversitesi, 2022)
Since the 1970s, the aseismic design of structures has greatly benefited from the application of seismic control systems. Seismic isolation is used to protect the structural and non-structural components as well as the contents of structures. The triple friction pendulum bearings (TFPBs) have attracted the attention of engineers and researchers due to their adaptive performance. Triple Friction Pendulum Bearings (TFB) are seismic isolators which have four concave sliding surfaces. Radius of curvature and friction coefficients of these surfaces are adjusted to meet the performance objectives of the seismic isolation system. This study aims to investigate the effect of contact surface friction on the seismic response of structures on Triple Friction Pendulum Bearings under near-fault and far-fault earthquakes through a parametric study. Generally, the results of the analysis have shown that increasing the value of the coefficient of friction mostly decreases the bearing displacements and increases the story accelerations. It has also been found that the effect of increasing the friction coefficient had a more profound influence on the seismic response parameters for the isolated structure subjected to near-fault earthquake ground motions.
Yüzey Sürtünmesinin Üçlü Sürtünmeli Sarkaç Mesnetli Yapıların Deprem Yükleri Altında Davranışına Etkisi
▪ Yüksek lisans tezi.
Keywords: Seismic Isolation; Triple friction pendulum system; OpenSEES; Seismic Response; Earthquake Resistant Design; Ground Motion Records